The Practical Value of Theory: Teaching Aristotle's "Poetics" to Screenwriters (Communication & Society, 2011)
This paper uses P. Ricoeur’s studies on the Poetics, and his notion of "refiguration" as developed in the work of Juan José García-Noblejas, under the scope of the Aristotelian doctrine. It suggests that the “first writing” of a screenplay focuses on the structure of the plot and the characters, dialogue and actions. The “re-writing” deals with these same elements; but above all, discovers the deep poetic structure that holds together the story. From that point on, the writer is able to return to the plot and refine it. This back and forth movement ends up in coherence and unity of the story, and so illuminates the writer’s personal exploration on the meaning of life.